EFFECT OF EPIDERMAL GROWTH FACTOR AND INSULIN ON IN VITRO MATURATION OF CAPRINE OOCYTES AND PRE IMPLANTATION EMBRYO DEVELOPMENT - PALANISAMMI, A; RANGASAMY, S; REENA, D; GOPIKRISHNAN, D (The Indian Journal of Animal Reproduction, 2023)
Totally 1362 oocytes were collected from 358 goat ovaries obtained from abattoir, by slicing technique. The overall culturable oocytes recovery rate per ovary was 2.02.ln experiment l(EGF @ 10 ng per ml), the number of inseminated oocytes cleaved day 1-2 were 145 embryos at 2-4 cell stage, 112 embryos at 8 cell stage on day 3, 75 embryos at 16-32 cell stage on day 4-5, 46 embryos at blastocyst stage on day 6-7.ln experiment ll(insulin@ 1 μg per ml), the number of inseminated oocytes cleaved at day 1-2 were 151 embryos at 2-4 cell stage, 123 embryos at 8 cell stage on day 3, 83 embryos at 16-32 cell stage on day 4-5 and 57 embryos at blastocyst stage on days 6-7.lnexperiment Ill (control) the number of inseminated oocytes cleaved at day 1-2 were 154 embryos at 2-3 cell stage, 98 embryos at 8 cell stage on day 3, 62 embryos at 16-32 cell stage on day 4-5 and 31 embryos at blastocyst stage on day 6-7. Thus supplementationof growth factors EGF and insulin to maturation and culture media can increase in vitro maturation rate and improve the embryo development rate in caprine.